Peran Orang Tua Terhadap Pembelajaran Daring Anak Usia Dini Pada Masa Pandemi Covid -19 - Ramadan, Novia (Universitas Muhammadiyah Sumatera Utara, 2021)
The COVID-19 pandemic that has occurred in almost all parts of the world has had a fairly serious impact. Not only the economy, health and security, but educational activities are also directly affected. The influence of Covid-19 can stop the direct learning process (face-to-face) in the world of education, giving a big impact on the mentality of early childhood. The learning process for early childhood during the COVID-19 pandemic will run well if teachers (as educators in schools) and parents coordinate with each other and participate cooperatively well. The provision of adequate facilities and infrastructure from parents at home is also important to help the online learning process to be carried out better. This success can be seen from the enthusiasm of the children in the learning process